Exploring algebraic change and relationship: A qualitative study for aspiring mathematics teachers - Suratman, Dede; Yusmin, Edy; Sayu, Silvia; Meldi, Nadya Febriani; Fitriawan, Dona (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Background: This study stems from the necessity to explore the proficiency in algebraic change and relationship among sixth-semester pre-service mathematics teachers, considering they have comprehensively encountered most mathematics content subjects. Aim: The primary aim is to delineate the ability of change and relationship in algebraic material and identify common errors, thereby contributing insights to enhance the overall quality of mathematics education.Method: Employing a qualitative descriptive approach, this research involved eight students selected based on their responses to instrument questions. The instrument utilized high-level essay questions, validated with a PISA orientation and developed in alignment with the assimilation of new knowledge specific to local students. Data were analyzed descriptively using Miles and Huberman’s model.Result: Findings revealed that when confronted with PISA-level questions equivalent to junior high school level, participants exhibited difficulties, making errors in calculations, concepts, information accuracy, and in connecting or converting the given information.Conclusion: The study underscores the imperative for holistic guidance on high-level questions like PISA for aspiring mathematics teachers, serving as a catalyst for educational innovation, particularly in mathematics education.